U.S. Total Factor Productivity Slowdown : Evidence from the U.S. States - Cardarelli, Roberto (IMF Working Papers; Working Paper ;, 2015)
Total factor productivity (TFP) growth began slowing in the United States in the mid-2000s, before the Great Recession. To many, the main culprit is the fading positive impact of the information technology (IT) revolution that took place in the 1990s. But our estimates of TFP growth across the U.S. states reveal that the slowdown in TFP was quite widespread and not particularly stronger in IT-producing states or in those with a relatively more intensive usage of IT. An alternative explanation offered in this paper is that the slowdown in U.S. TFP growth reflects a loss of efficiency or market dynamism over the last two decades. Indeed, there are large differences in production efficiency across U.S. states, with the states having better educational attainment and greater investment in R and D being closer to the production 'frontier.'.